ANALISA UNSUR-UNSUR PEMBELAAN TERPAKSA DALAM SUATU TINDAK PIDANA DENGAN STUDI KASUS PUTUSAN PENGADILAN NEGERI KEPANJEN NOMOR. 01/PID.SUS-ANAK/2020/PN.KPN - Stanislaus Arthur R.W.; R Rahaditya (Jurnal Hukum Adigama, 2021)
Basically, self-defense is a right which becomes the instinct of every person to defend himself or others, his property and honor from the evil deeds of other parties, which want to destroy or harm them illegally. The Criminal Code regulates several legal defenses, including the Overmacht which is regulated in Article 48 of the Criminal Code (KUHP), Noodtoestand and Noodweer which are regulated in Article 49 paragraph 2. This writing raises the issue of how the implementation of the defense is forced to become excuses for forgiveness and reasons for eliminating crime in Article 49 paragraph 2 of the District Court Decision Number 01 / PID.SUS-ANAK / 2020 / PN.KPN. This writing uses a normative or doctrinal research method, namely research provides a systematic explanation of the rules governing a category, the nature of research which uses practical and prescriptive normative properties, the types and techniques of writing are primary and secondary legal materials. noodweer excess in this case cannot be used as an excuse to abolish a crime because the judge does not have a proper basis in determining the decision.